Peningkatan Hasil Belajar Siswa melalui Model Pembelajaran Berbasis Proyek Berbantuan Aplikasi Wordwall pada Materi Tata Surya di Sekolah Dasar - Isnanto, Isnanto; Ahmad, Widyastuti; Kudus, Kudus (SITTAH: Journal of Primary Education, 2024)
The problem behind this research begins with 63% of students not having reached the KKM and learning not being fully focused on students. This research aims to describe the use of the PjBL model assisted by the Wordwall application to improve student learning outcomes. The research method used is Classroom Action Research (PTK) in one of the State Elementary Schools in South City, Gorontalo City. Data were collected through observation, interviews, documentation and tests with research subjects consisting of students of Class VI at SDN No. 25 Kota Selatan. The results showed that out of a total of 16 students, 6 students (37%) achieved the passing grade, while 10 students (63%) did not achieve the passing grade. In Cycle I, the number of students who achieved the passing grade increased to 9 (56%), while the number of students who did not achieve the passing grade decreased to 7 (44%). Moreover, in the second cycle of the action, there was a significant increase, with 15 students or 94% achieving the passing grade, while 1 student or 6% did not achieve the passing grade. The research results showed that there was a change, namely from 63% to 94% of students who were declared to have achieved the KKM. Thus, it can be concluded that the use of the PiBL (Project-Based Learning) model, assisted by the Wordwall application, bas the potential to improve students' learning outcomes on solar system topic in Class VI SDN No. 25 Kota Selatan.